The relationships of celebrity, individual characteristics and attitude on intention to imitate Korean celebrity behaviour - Wan Roazha Wan Mat (2019)
Marketers always look for opportunities to promote their type of brand and product by using celebrity endorsement to deliver their objectives. Nowadays, Korean celebrities have become very popular among Malaysian and also around the world. This is a good chance for marketers to use the Korean celebrity to appear in advertisements to endorsing their product or brand. Using the celebrity endorsement in advertisement is successful. Therefore, this situation has encourage the current study to addresses the issue of young Malaysians' intention to imitate Korean celebrity endorsement behaviour in an advertisement. Specifically, it indicates the influence of Korean celebrity endorsement in an advertisement on consumer's attitude toward imitating Korean celebrity endorsement and has an impact on their intention to imitate Korean celebrity behaviour. In this study, the researcher focuses on the impact of Korean celebrity's characteristics (attractiveness, credibility, trustworthiness and expertise) and consumer's individual characteristics (self-satisfaction and expression of power) on the Malaysian consumers' attitude towards imitating Korean celebrity endorsement and this leads to Malaysian consumer's intention to imitate Korean celebrity behaviour. The theory of para-social interaction proposed by Horton and Wohl (1956) and theory of imitation proposed by Tarde (1969) and Baldwin (1925) were used in this study to support the conceptual framework used in this study. Six hundred Malaysian university students from around the Klang Valley participated in this study. Using Smart-PLS version 3 .2. 7 to analyse the data and the results shown that Korean celebrity's characteristics which consist of attractiveness and trustworthiness are significant while credibility and expertise are not significant predictors on consumer attitude toward imitating Korean celebrity endorsement. However, consumer's individually characteristics which consist of both self-satisfaction and expression of power are significant predictors on consumer attitude toward imitating Korean celebrity endorsement. Besides, there was a significant effect of attitude toward imitating Korean celebrity endorsement on intention to imitate Korean celebrity behaviour. Finally, the attitude toward imitating Korean celebrity endorsement was also found to significantly mediate the relationship between self-satisfaction and expression of power and intention to imitate Korean celebrity behaviour, although, the attitude toward imitating Korean celebrity endorsement was also found to significantly mediate the relationship between (attractiveness and trustworthiness) and intention to imitate Korean celebrity behaviour. But, the attitude toward imitating Korean celebrity celebrity endorsement was found not significantly to mediate the relationship between (credibility and expertise) and intention to imitate Korean celebrity behaviour. Suggestions for future research and practitioners are also discussed.